Carbon monoxide and carbon dioxide adsorption on alkali metal cation‐exchanged SSZ‐13 zeolites. (22nd July 2020) - Feng, Jiawei; Hu, Yunfeng; Bao, Qiang; Liang, Dan; Xu, Ying
Abstract : In this work, chabazite SSZ‐13 samples with different cations were synthesised by hydrothermal method and thoroughly analysed using various characterisation techniques. The role of types of cations in CO2 and CO adsorption measurements was investigated. The adsorption isotherms were fitted by Langmuir, Langmuir‐Freundlich and Toth adsorption models, respectively. The result shows that the Langmuir‐Freundlich model is the most suitable for the adsorption isotherms of SSZ‐13 molecular sieves. The adsorption isotherms of the fitted CO2 and CO were analysed to study the high silicon SSZ‐13 samples of alkali metal cations Li +, Na +, K + and Cs + for ion exchange. The result shows that Na + has the highest adsorption capacity, but the adsorption selectivity is extremely low. K + has the lowest adsorption capacity, but it has excellent adsorption selectivity, which may be attributed to its large cation radius and the special position of cations in CHA skeleton structure, resulting in the formation of 'molecular trapdoor' effect. In addition, Cs + has a larger ionic radius than K +, but the adsorption selectivity is not significantly improved, similar to Li + . It can be determined that the 'molecular trapdoor' effect has a significant relationship with the position of cations in the framework.